Barriers and Opportunities of Implementing Flipped Classroom in Teaching Reading Comprehension of Literature in Vietnamese High Schools - Oanh Ngoc Tran Ho (Philippine Social Science Journal, 2025)
This mixed-methods study investigates the awareness, readiness, and engagement regarding the Flipped Classroom (FC) model among 55 high school Literature teachers and 156 students in central Vietnam. Although results indicated high teacher awareness and willingness to adopt the model, actual implementation remained low (21.8%) due to resource constraints and challenges in monitoring student self-regulation. Similarly, students reported barriers regarding independent learning habits and digital access, despite statistical analysis revealing a strong correlation between self-directed learning skills and engagement. The findings suggest that while the FC model holds promise for enhancing critical thinking in Literature education, widespread adoption requires robust institutional support, improved digital infrastructure, and targeted training to bridge the gap between theoretical readiness and practical application.